MANAJEMEN PENGEMBANGAN KURIKULUM DI SMP NEGERI 2 TELUK PANDAN - Robinson, Amos (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research aims to analyze and describe the curriculum development at SMP Negeri 2 Teluk Pandan, East Kutai Regency. The research type is descriptive qualitative. The subjects of this research are the school principal, teachers, school committee, student guardians, and students. The research object is curriculum development management, which includes planning, organizing, implementing, and supervising. Data collection techniques use observation, interviews, and documentation. Qualitative data analysis uses the interactive model of Miles and Huberman, which includes data collection, data condensation, data display, and conclusion drawing. The validity test uses the triangulation technique. The research results on the aspects of curriculum development management are: 1) Planning, which involves developing the vision, mission, and goals, preparing programs, facilities and infrastructure, learning tools, and human resources; 2) Organizing, which covers the management of institutional structure, regulations, work programs, human resources, activity units, facilities and infrastructure, budget, partnerships, supervision, and evaluation; 3) Implementation, where learning uses contextual and scientific approaches, with methods such as exposition, reflective thinking, discussion, and simulation. The learning materials are systematically arranged and cross-curricular, including extracurricular activities; 4) Supervision, which is carried out through internal audit activities in the form of direct and indirect supervision, with supervision targets covering planning, management, education, empowerment of the school community, and the physical school. ABSTRAK Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan pengembangan kurikulum di SMP Negeri 2 Teluk Pandan Kabupaten Kutai Timur. Jenis penelitian kualitatif deskriptif. Subyek penelitian adalah kepala Sekolah, guru, komite, wali siswa dan siswa. Obyek penelitian adalah manajemen pengembangan kurikulum meliputi perencanaan, pengorganisasian, pelaksanaan, dan pengawasan. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Analisis data kualitatif menggunakan model interaktif Miles dan Huberman meliputi pengumpulan data, kondensasi data, display data, dan penarikan kesimpulan. Uji Keabsahan menggunakan teknik triangulasi. Hasil penelitian manajemen pengembangan kurikulum aspek: 1) Perencanaan berupa pengembangkan visi misi dan tujuan, penyusunan program, sarana dan prasarana, perangkat pembelajaran dan SDM; 2) Pengorganisasian mencakup pengelolaan struktur kelembagaan peraturan, program kerja, SDM, unit-unit kegiatan, sarana prasana, anggaran, kemitraan, pengawasan dan evaluasi; 3) Pelaksanaan pembelajaran menggunakan pendekatan kontekstual dan ilmiah, dengan metode eksposisi, berpikir reflektif, diskusi, simulasi. Materi pembelajaran disusun secara sistematis dan lintas mata pelajaran dan ekstrakurikuler. 4) Pengawasan melalui kegiatan audit internal, dalam bentuk pengawasan langsung dan tidak langung, dengan sasaran pengawasan meliputi perencanaan, manajemen, pendidikan, pemberdayaan warga sekolah dan fisik sekolah.